Connecting Transculturalism with Transformative Learning: Toward a New Horizon of Adult Education - Jurkova, Sinela; Guo, Shibao (Alberta Journal of Educational Research, 2018)
The impact of transnational migration with activities across transnational borders has reconfigured multiple social and public identities calling for shifting to transculturalism as a theoretical framework in understanding the changing nature of adult education. Transculturalism becomes a mode of being and learning where humans interact with each other in a culturally diverse environment. Integrating different identities and connecting the global with the local, transculturalism is a learning commitment that facilitates socio-cultural adaptation and interaction in a dynamic society recognizing different worldviews. This paper offers a theoretical approach toward transculturalism as transformative learning with a focus on discussions of cultural concepts and connections with perspective transformation. The common ground between transculturalism and transformative learning is the idea of continuum, and interconnection of knowledge, skills and attitudes as an ongoing process of inquiry, thinking, reflecting, and acting. Connecting theories of transculturalism and transformative learning with our new reality of transnational mobility across the world opens new horizons for policies and practices in immigration and adult education. L’impact de la migration transnationale et les activités transfrontalières qui en découlent a reconfiguré de multiples identités sociales et publiques, provoquant ainsi une demande d’adopter le transculturalisme comme cadre théorique pour comprendre l’évolution de l’éducation des adultes. Le transculturalisme devient un mode d’être et d’apprentissage où les humains interagissent dans un milieu culturellement diversifié. Intégrant différentes identités et liant le mondial au local, le transculturalisme est un engagement à l’apprentissage qui facilite l’adaptation et l’interaction socioculturelles dans une société dynamique qui reconnait la pluralité des visions du monde. Cet article offre une approche théorique qui considère le transculturalisme comme un apprentissage transformationnel axé sur les discussions de concepts et de liens culturels visant une transformation des perspectives. Le terrain commun entre le transculturalisme et l’apprentissage transformationnel est l’idée de continuum et l’interconnexion des connaissances, habiletés et attitudes comme processus continu d’enquête, de réflexion et d’actions. Le fait de lier les théories du transculturalisme et de l’apprentissage transformationnel à notre nouvelle réalité de mobilité transnationale de par le monde ouvre de nouveaux horizons aux politiques et aux pratiques touchant l’immigration et l’éducation des adultes. Mots clés : transnationalisme, transculturalisme, apprentissage transculturel, transformation des perspectives